Pengembangan Instrumen Evaluasi Tarkib - Abdul Malik Fajarudin; Fatimah Azzahra Putri; Raswan; Ubaid Ridho (Rayah Al-Islam, 2026)
This study is motivated by the dominance of conventional tarkib (Arabic grammar) tests that emphasise rule memorisation and iʿrāb analysis, so they do not yet reflect learners’ ability to use sentence structures communicatively. It aims to describe the conceptual development of a CEFR-oriented evaluation instrument for tarkib and to map syntactic ability indicators across proficiency levels. Using qualitative, descriptive library research with content analysis of key works on Arabic language testing and language assessment design, the study formulates hierarchically ordered indicators of tarkib ability from A1 to C2 based on accuracy, structural complexity, and contextual appropriateness. The findings also organise representative item formats multiple choice, completion, sentence transformation, error recognition and correction, iʿrāb analysis, and productive sentence-making into a coherent blueprint for communicative tarkib assessment that can guide teachers and curriculum designers in constructing more diagnostic, level-sensitive tests.